Nuclear trafficking - Zaitseva, Lyudmila (Henry Stewart Talks, 2009)
Threats, DSTO, Case distribution by material, Nuclear material, Radioactive material, Trend analysis, DSTO incidents: 1991-2008, HEU and Pu-239, Profit-motivated cases, Police/intelligence operations, Policing vs. border control, Involvement of organized crime, View from Russia, Changing nature of OC, UN convention against transnational OC, Dataset and selection criteria, OC cases by year: 1999-2008, HEU seizures, OC cases by country, Actors, Nationals involved, Ukrainian smuggling rings, Turkey: interim destination, Supply/Demand driven market, Links to drugs and weapons
Archived at 2022/04/03